Kyai Leadership in Developing Islamic Boarding School Agribusiness - Sunaji, Sunaji; Wanto, Wanto; Wasis, Wasis (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
Islamic boarding schools are a place to develop human qualities so that they become people with good character and noble morals, but Islamic boarding schools need to develop their entrepreneurship to be able to cover education better. This research aims to collaborate on three things, namely: the concept of the leadership role of Kyai in the development of Islamic boarding school agribusiness, developing entrepreneurship in Islamic boarding schools and the benefits that Islamic boarding schools and the surrounding community gain from developing entrepreneurship in Islamic boarding schools. This data was obtained from an Islamic boarding school that has successfully developed entrepreneurship, namely the Sunan Drajat Islamic boarding school. Researchers conducted this research by means of observation interviews and documentation. Data analyzed using domain and component analysis techniques. The results of this data analysis show that the concept of a Kyai in developing agribusiness in Islamic boarding schools is a collective, democratic and consultative form. Meanwhile, the strategy carried out by a Kyai is to build and maintain a form of trust, empowerment, synergy, flexible policy innovation to form solid cooperation. The benefits of developing entrepreneurship or agribusiness in this Islamic boarding school are felt and enjoyed by many elements, including all levels of society around the Santri and all extended families of the Islamic boarding school.